Overflow Characteristic of Cylindrical Shape Crest Weirs Over Horizontal Bed - Emad4 AbdulGabbar (Tikrit Journal of Engineering Sciences, 2013)
The most common types of weirs are the broad-crested weir, the sharp-crested weir, the circular crested weir and the ogee crested weir. Advantages of the cylindrical weir shape include the stable overflow pattern, the ease to pass floating debris, the simplicity of design compared to ogee crest design and the associated lower costs. In present study, it was investigated the overflow characteristics of circular weirs in laboratory for various cylinder radii of three sizes (11.4, 9.0, 6.3 cm), and the models fixed on the channel bed vertically to the direction of flow. The result shows that the increase in the ratio of head to weir radius ratio (Hw/R) value causes an increase in discharge coefficient (Cd) value for the same height of weir. It was observed that the cylinder size (i.e. radius of cylindrical weir (R)) has an effect on the (Cd). The flow magnification factor (qw/qs) increases with an increase in (Hw/R) value and values of (qw/qs) were always higher than one for all values of (Hw/R), this means that weirs of cylindrical shape performed better than those of sharp crest for any value of weir radius tested in this study.